Analisis Pengelolaan Sampah Terpadu (Studi Kasus: Kabupaten Bireuen) - Elvida, Desi; Rahmat Abbas; Cut Azizah` (Jurnal Serambi Engineering, 2025)
The waste problem is in the national spotlight as the population grows every year and more and more waste is produced. Waste management in Bireuen Regency is still based on the old paradigm of collection-transport-disposal, with waste management services focused only on urban areas. The transported waste is simply dumped in the landfill and incinerated. This research aims to determine the waste management system in Bireuen Regency. The method used in this research is observation and interviews regarding the operational system of waste management and calculation of waste generation based on estimates of waste generation. The research results show that the amount of waste produced based on the estimated waste generation is 221,937 kg/day, while the amount of waste transported is 52,316.5 kg/day. The existing waste management system in Bireuen Regency still follows the old paradigm of collect-transport-disposal. An integrated waste management system in accordance with Law 18 of 2008, namely reduction and treatment.